Tokoh Mitologi dalam Mantra Nyangahatn Ka’ Saka’ Panen Padi Etnis Dayak di Kalimantan Barat - Herlina Herlina; Sri Kusnita; Try Hariadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The mythological figure referred to in this study is related to a figure who is considered holy and is considered to have the power to help even bring disaster to humans. The mention of a mythological figure when reciting the mantra Nyangahatn Ka 'Saka' rice harvest for the Dayak ethnic group in West Kalimantan is always mentioned repeatedly in every rice harvest mantra, both in the pre-ritual, ritual and post-ritual mantra. The mention of mythological figures is intended to communicate so that they can bring help to humans during the process of carrying out the rice harvest ritual. This study aims to describe the mythological figures during the chanting of the Dayak ethnic rice harvest ceremony in West Kalimantan. Using the form of descriptive qualitative research using the method of recording and recording during the process of reciting the mantra of the rice harvest ceremony. The results of this study indicate that in the recitation of the rice harvest mantra, there is mention of mythological figures in the mention of the name Jubata, Bujakng Baparas and the use of the pronoun Kalian to refer to supernatural beings. The mention of the name Jubata refers to everything that can bring goodness to mankind. The mention of Bujakng Baparas refers to supernatural beings who can help and bring disaster to humans, can also act as an intermediary for human communication with supernatural beings around human life, while the use of the pronoun Anda refers to other supernatural beings believed to inhabit water and land areas and are believed to be able to bring help and disaster.